The relationship between job performance, job security, organizational support, rewards and job satisfaction among medical doctors in Pakistan - Khan, Mirwise (2015)
The defense of necessity has traditionally been conceived as providing a utilitarian justification for what would otherwise be poor performance at working place. In the medical field, hence, the nature of the justification has hitherto been based upon a concern to respect medical doctors’ rights. Recent concern about doctor’s job performance has intensifies interest in public hospitals and private clinics. In Pakistan, medical doctors are facing several problems related with job security, organizational support, and reward and job satisfaction. They are on strikes and demanding their rights. It is important to find out the reason for resolving the persistent issues. This study examined the relationships between job security, organizational support, reward, job satisfaction and medical doctor’s job performance in public hospitals and private clinics in Pakistan. The study also examined the mediating effect of job satisfaction on these relationships. A cross-sectional survey method is used to conduct this study. Questionnaires are distributed to 400 medical doctors in Pakistan, and 275 were returned, giving a response rate of 69 percent. Results of the study revealed that the job security, organizational support, reward and job satisfaction has a significant, positive relationship with job performance. Furthermore, the results showed that job satisfaction has a mediating effect on the relationship between job security and job performance. Job satisfaction has a mediating effect on the relationship between organizational support and job performance. Moreover, job satisfaction has a mediating effect on the relationship between reward and job performance. Based on the results, this study is contribution to policy makers to take some assistance for resolving the existing issues and ensuring the job security organizational support, and reward and job satisfaction for medical doctors which would fetch improvement in medical doctor’s job performance.